Pharmacodynamics and Pharmacokinetics of Ublituximab Compared with Other Anti-CD20 Monoclonal Antibodies for Multiple Sclerosis Treatment - Margoni, Monica; Battistini, Luca; Centonze, Diego; Furlan, Roberto; Gasperini, Claudio; Filippi, Massimo (Current Neuropharmacology, 2025)
The therapeutic scenario for multiple sclerosis (MS) has expanded rapidly over the last few years. Among the available treatments, anti-CD20 monoclonal antibodies, including rituximab, ocrelizumab, ofatumumab, and ublituximab, have shown significant results in reducing disease activity and slowing progression, particularly in relapsing MS. The distinct mechanisms of action, including the pharmacokinetic and pharmacodynamic profiles as well as the immunogenicity of these drugs, require careful consideration to tailor treatment for individual patients. A comprehensive review of the literature was conducted by searching PubMed and evaluating key studies, trials, and congress abstracts related to the use of anti-CD20 monoclonal antibodies. The analysis focused on the pharmacokinetic and pharmacodynamic profiles, as well as the immunogenicity, of anti-CD20 therapies currently available, with particular emphasis on the recently approved ublituximab. Ocrelizumab is effective in both relapsing-remitting and primary-progressive MS, using antibody-dependent cellular cytotoxicity (ADCC) as its primary mechanism of action, with intravenous and subcutaneous administration options ensuring flexible treatment delivery. Ofatumumab depletes B-cells through enhanced complement-dependent cytotoxicity, offering convenient monthly subcutaneous self-administration. Ublituximab’s unique glycoengineered fragment crystallizable region enhances ADCC, resulting in rapid B-cell depletion and potentially improving its safety profile. Ublituximab allows for a shorter infusion time without requiring post-infusion monitoring after the second dose, provided there have been no prior reactions. Understanding the characteristics of different anti-CD20 monoclonal antibodies is critical for optimizing treatment, enhancing patient outcomes, and minimizing treatment burden. Ublituximab represents a promising option, offering a shorter infusion time and higher ADCC activity, which complements existing treatments such as ocrelizumab and ofatumumab.
Keywords: anti-CD20 therapy